Oxytocin and socioemotional aging: Current knowledge and future trends - Ebner, Natalie C.; Maura, Gabriela M.; Macdonald, Kai; Westberg, Lars; Fischer, Håkan (Frontiers in Human Neuroscience, 2013)
The oxytocin (OT) system is involved in various aspects of social cognition and prosocial behavior. Specifically, OT has been examined in the context of social memory, emotion recognition, cooperation, trust, empathy, and bonding, and─though evidence is somewhat mixed─intranasal OT appears to benefit aspects of socioemotional functioning. However, most of the extant data on aging and OT is from animal research and human OT research has focused largely on young adults. As such, though we know that various socioemotional capacities change with age, we know little about whether age-related changes in the OT system may underlie age-related differences in socioemotional functioning. In this review, we take a genetic-neuro-behavioral approach and evaluate current evidence on age-related changes in the OT system as well as the putative effects of these alterations on age-related socioemotional functioning. Looking forward, we identify informational gaps and propose an Age-Related Genetic, Neurobiological, Sociobehavioral Model of Oxytocin (AGeNeS-OT model) which may structure and inform investigations into aging-related genetic, neural, and sociocognitive processes related to OT. As an exemplar of the use of the model, we report exploratory data suggesting differences in socioemotional processing associated with genetic variation in the oxytocin receptor gene (OXTR) in samples of young and older adults. Information gained from this arena has translational potential in depression, social stress, and anxiety─all of which have high relevance in aging─and may contribute to reducing social isolation and improving well-being of individuals across the lifespan.